One‐year results from a prospective randomized trial comparing phlebotomy with deferasirox for the treatment of iron overload in pediatric patients with thalassemia major following curative stem cell transplantation. Issue 1 (31st August 2016) - Inati, Adlette; Kahale, Mario; Sbeiti, Nada; Cappellini, Maria Domenica; Taher, Ali T.; Koussa, Suzanne; Nasr, Therese A.; Musallam, Khaled M.; Abbas, Hussein A.; Porter, John B.
Abstract: Background: Iron overload is well documented in patients with β‐thalassemia major, and patients who have undergone hematopoietic stem cell transplantation (HSCT) remain at risk as a result of pre‐ and immediate post‐HSCT transfusions. Procedure: This is a prospective, randomized, 1‐year clinical trial that compares the efficacy and safety of the once‐daily oral iron chelator deferasirox versus phlebotomy for the treatment of iron overload in children with β‐thalassemia major following HSCT. Results: Patients (aged 12.4 years) received deferasirox (n = 12, 10 mg/kg/day starting dose) or phlebotomy (n = 14, 6 ml/kg/2 weeks) for 1 year. In two and five patients, deferasirox dose was increased to 15 and 20 mg/kg/day, respectively. Magnetic resonance imaging (MRI)–assessed liver iron concentration (LIC) decreased with deferasirox (mean 12.5 ± 10.1 to 8.5 ± 9.3 mg Fe/g dry weight [dw]; P = 0.0005 vs. baseline) and phlebotomy (10.2 ± 6.8 to 8.3 ± 9.2 mg Fe/g dw; P = 0.05). LIC reductions were greater with deferasirox than with phlebotomy for patients with baseline serum ferritin 1, 000 ng/ml or higher (–8.1 ± 1.5 vs. –3.5 ± 5.7 mg Fe/g dw; P = 0.048). Serum ferritin and non‐transferrin‐bound iron also decreased significantly. In two patients with severe cardiac siderosis, a clinically relevant improvement in myocardial T2* was seen, following phlebotomy and deferasirox therapy (n = 1 each). Adverse effects with deferasirox were skin rash, gastrointestinal upset, and increased liver function tests (all n = 1), while those for phlebotomy were difficulty with venous access (n = 4) and distress during procedure (n = 1). Parents of 13/14 children receiving phlebotomy wished to switch to deferasirox, with 1/14 being satisfied with phlebotomy. Conclusions: Deferasirox treatment or phlebotomy reduces iron burden in pediatric patients with β‐ thalassemia major post‐HSCT, with a manageable safety profile.